2009
DOI: 10.1177/1066896909339184
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Subtypes of Penile Squamous Cell Carcinoma From High and Low Incidence Geographical Regions

Abstract: There is a worldwide geographical variation in the incidence of penile squamous cell carcinoma (PSCC); some subtypes are HPV-related (warty, basaloid) while others (keratinizing variants) are not. The aims of this study were to compare the distribution of different histological subtypes of PSCC from regions of low (Paraguay, 144 cases) and high (USA, 157 cases) incidence and to identify and compare tumors with and without warty and/or basaloid morphology. The distribution of subtypes in the Paraguayan and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 45 publications
1
14
1
Order By: Relevance
“…The finding may be an indication of ethnic or cultural (late diagnosis) geographic differences among countries. The differences are more likely restricted to mortality and not to relative frequencies of histological subtypes since in other studies we found no geographical differences in the distribution of histological subtypes of penile SCCs, including the basaloid carcinomas [31,32]. There is a recent study suggesting a higher frequency of HPV-related carcinomas, among them the basaloid tumors, in African patients comparing to patients from other continents with the same tumor subtypes [19].…”
Section: Discussionmentioning
confidence: 84%
“…The finding may be an indication of ethnic or cultural (late diagnosis) geographic differences among countries. The differences are more likely restricted to mortality and not to relative frequencies of histological subtypes since in other studies we found no geographical differences in the distribution of histological subtypes of penile SCCs, including the basaloid carcinomas [31,32]. There is a recent study suggesting a higher frequency of HPV-related carcinomas, among them the basaloid tumors, in African patients comparing to patients from other continents with the same tumor subtypes [19].…”
Section: Discussionmentioning
confidence: 84%
“…9,18,19 Other mixed forms of penile squamous cell carcinomas have been reported as part of larger series. 9,17 We are describing a hitherto poorly recognized mixed neoplasm exhibiting warty and basaloid features. Considering their common human papillomavirus-related pathogenesis and the existence of morphological mixed forms, warty and basaloid carcinomas would represent the low-and high-grade ends of a clinicopathological spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…3,17 Often it is problematic to classify and evaluate the prognostic significance of these mixed variants. Well known is the mixed usual-verrucous (hybrid) carcinoma with its increased risk for nodal metastasis when compared with pure verrucous carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the incidence of penile and cervical cancers is high in the same geographical areas, it is reasonable to assume that both types of cancer share the same etiological factors. However, less than half of penile cancers are related to HPV infection (Gross & Pfister, 2004;Rubin et al, 2001) whereas the virus is found in almost all cervical SCCs (Chaux et al, 2010).…”
Section: High Risk Hpv-associated Penile Cancermentioning
confidence: 99%